2019
DOI: 10.1038/s41396-019-0359-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Evolution of substrate-specific gene expression and RNA editing in brown rot wood-decaying fungi

Abstract: Fungi that decay wood have characteristic associations with certain tree species, but the mechanistic bases for these associations are poorly understood. We studied substrate-specific gene expression and RNA editing in six species of wooddecaying fungi from the 'Antrodia clade' (Polyporales, Agaricomycetes) on three different wood substrates (pine, spruce, and aspen) in submerged cultures. We identified dozens to hundreds of substrate-biased genes (i.e., genes that are significantly upregulated in one substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 74 publications
2
29
0
Order By: Relevance
“…In these fungi, editing has been reported to diversify transcripts coding for enzymes that are required for the degradation of wood (Zhu et al 2014;Wu et al 2018). A comparative study using the wood-decaying fungi Antrodia sinuosa, Daedalea quercina, Fomitopsis pinicola, Laetiporus sulphureus, and Wolfiporia cocos found an effect of different substrates on editing positions and frequency (Wu et al 2019).…”
Section: Types and Occurrence Of Mrna Editingmentioning
confidence: 99%
“…In these fungi, editing has been reported to diversify transcripts coding for enzymes that are required for the degradation of wood (Zhu et al 2014;Wu et al 2018). A comparative study using the wood-decaying fungi Antrodia sinuosa, Daedalea quercina, Fomitopsis pinicola, Laetiporus sulphureus, and Wolfiporia cocos found an effect of different substrates on editing positions and frequency (Wu et al 2019).…”
Section: Types and Occurrence Of Mrna Editingmentioning
confidence: 99%
“…Our results show that RNA editing not only occurs in fruiting, but also other developmental paths. Similar to the stage-specific and substrate-specific RNA editing studies on basidiomycetes, editing events in C. cinerea regulate the genes in carbohydrate metabolism and cell structure formation (37, 38). All these results emphasize the functional similarity of RNA editing in regulating carbohydrate metabolism, and further, the essential role of carbon metabolism in fungal development.…”
Section: Discussionmentioning
confidence: 88%
“…Vegetative mycelium grows in changeable environment and it is in charge of primary occupation of new habitat. The Agaricales-specific and species unique genes are very likely to benefit the fungus on niche segmentation and adapting to the complex and changing environment during vegetative growth (38, 67, 68). High expression on species-specific genes and relative lower selective pressure of purifying selection enable mycelium to minimize the interspecific competition and improve fitness (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant biomass is recognized as a sustainable source of mixed sugars for fermentation to second generation biofuels and high-value molecules. Fungi have evolved different strategies to degrade lignocellulose [53][54][55][56][57][58]. The genome of the thermophilic fungus C. thermophilum suggested that this fungus should prefer to degrade monocots that are rich in cellulose, xylan and β-glucan.…”
Section: Discussionmentioning
confidence: 99%